2005
DOI: 10.1097/01.inf.0000180471.03702.7f
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characteristics of Viral Infections in a Neonatal Intensive Care Unit During a 12-Year Period

Abstract: The incidence of viral infection in the NICU was 1%. Enteroviral infections were the most frequently diagnosed infections, occurred often in term infants born at home and presented with sepsis-like illness or seizures. Preterm infants hospitalized from birth mainly developed gastrointestinal disease caused by rotavirus and adenovirus infection or respiratory disease caused by RSV, parainfluenza and CMV infection. Enteroviruses were responsible for the highest mortality and development of serious sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 27 publications
1
78
1
1
Order By: Relevance
“…There are other viruses associated with congenital infections, such as rubella virus, cytomegalovirus, lymphocytic choriomeningitis virus, and human immunodeficiency virus, for example. Additional seasonal viruses, including influenza virus, respiratory syncytial virus (RSV), adenoviruses, rhinoviruses, and rotaviruses, have been identified in hospitalized neonates, related primarily to horizontal transmission (41). However, these pathogens are not typically associated with an EOS presentation.…”
Section: Pathogensmentioning
confidence: 99%
“…There are other viruses associated with congenital infections, such as rubella virus, cytomegalovirus, lymphocytic choriomeningitis virus, and human immunodeficiency virus, for example. Additional seasonal viruses, including influenza virus, respiratory syncytial virus (RSV), adenoviruses, rhinoviruses, and rotaviruses, have been identified in hospitalized neonates, related primarily to horizontal transmission (41). However, these pathogens are not typically associated with an EOS presentation.…”
Section: Pathogensmentioning
confidence: 99%
“…Therefore, due to the large number and types of viruses, identifying and deciphering the mechanism by which viral infection induces seizures have been challenging. For example, two members of the family Picornaviridae, Enterovirus (EV) and Parechovirus (PeV), have been shown to induce seizures in infected children; however, the available diagnostic tests for EVs do not detect PeVs (2,3). A recent retrospective study, using pediatric cerebrospinal fluid samples previously screened for EV, demonstrated that the inclusion of a novel PeV-specific PCR assay led to a 31% increase in the detection of viruses causing virally induced CNS symptoms and neonatal sepsis (4).…”
mentioning
confidence: 99%
“…Herpes simplex virus, cytomegalovirus, varicella-zoster virus, Epstein-Barr virus, human herpesvirus 6, and Kaposi's sarcoma-associated herpesvirus (KSHV) have all been associated with respiratory diseases (7,10,30,33,42,46). Much of our understanding of immune responses to viral infection of the respiratory tract comes from experimental animal models.…”
mentioning
confidence: 99%